1997
DOI: 10.1080/00288306.1997.9514747
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of dike rocks in Dun Mountain Ophiolite, Nelson, New Zealand

Abstract: Basaltic dikes of the Lee River Group (Permian) at Roding River and in the Red Hills ultramafic body, both parts of the Dun Mountain Ophiolite, were analysed for major and trace elements. The dikes in the Lee River Group change into massive and pillowed lava towards the uppermost part of the sequence. The dikes in the Red Hills occur parallel to the layering of host ultramafic rocks. The Red Hills ultramafic body corresponds to the mantle-crust transition zone. The age of Red Hills dikes has been determined at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
5
1
Order By: Relevance
“…It is difficult to explain why the spatial pattern of Sr concentrations shows the opposite trend to that of Ni and Cr given that Sr is also known to be elevated in the Red Hills ultramafic rock (Sano et al 1997). Sr concentrations in sediments collected from near the Motueka River mouth were in fact the lowest of any sites measured in the present study.…”
Section: Sediment Metalscontrasting
confidence: 72%
“…It is difficult to explain why the spatial pattern of Sr concentrations shows the opposite trend to that of Ni and Cr given that Sr is also known to be elevated in the Red Hills ultramafic rock (Sano et al 1997). Sr concentrations in sediments collected from near the Motueka River mouth were in fact the lowest of any sites measured in the present study.…”
Section: Sediment Metalscontrasting
confidence: 72%
“…The e Nd (T) values are similar to present-day marginal basin basalts (McCulloch et al 1980;Volpe et al 1987Volpe et al , 1988 (Fig. 2) and basalts from the Lee River Group (£Nd(T) = +7.5 to +8.3 at 280 Ma; Sano et al 1997). The stage 2 basalts have MORB-like Sr/Nd (7-10), Ti/Y (266), Zr/Y (3.2), Ti/Zr (90-100), Hf/Th (c. 12), and Ti/V (c. 30) (cf.…”
Section: Nd-isotope Systematics and Geochemistrymentioning
confidence: 67%
“…Moreover, the bulk of the siliceous plagiogranites are not differentiates of the isotopically distinct tholeiitic magmas that produced the ocean island basalt (OIB)-like to MORB-like basaltic lava suites also preserved in the ophiolite (indeed the lavas yield older ages; see below). Sano et al (1997) suggested that the Red Hills ultramafic body farther south in the DMOB, as well as basalt-plagiogranite dikes in the Red Hills complex, probably originated in an island arc related tectonic environment. The ophiolite stratigraphy itself, however, in no way resembles that in a normal arc, with well-defined "point source" volcanic edifices draped by substantial volcaniclastic aprons.…”
Section: Regional Geologymentioning
confidence: 97%
“…Supra-subduction zone ophiolites can form in both 'pre-arc' settings related to subduction initiation (prior to typical calc-alkaline arc magmatism) and also in rifted back-arc settings. Back-arc genesis has been proposed for the Dun Mountain ophiolite (Sano et al 1997;Sivell & McCulloch 2000;Jugum et al 2006) mainly on geochemical grounds. However, there is no evidence of the expected precursor volcanic arc (e.g.…”
Section: Ophiolite Remnants As Regionally Coherent Oceanic Crustmentioning
confidence: 99%